Isolation Improvement Technique for Two Closely Spaced Loop Antennas Using MTM Absorber Cells - Hongmin Lee; Hyungsup Lee (International Journal of Antennas and Propagation)
This paper presents a new method to improve isolation between two loop antennas with absorber cells exhibiting negative permittivity and permeability at the aimed frequency of 2.54 GHz. The metamaterial (MTM) unit cell was constructed by two open complementary split ring resonator (OCSRR) and a split ring resonator (SRR) arrangement. The proposed antenna structure consists of two loop antennas occupying a space with the dimensions of 51 mm×24 mm×2 mm and three absorber cells. The size of each absorber unit cell is 7.4 mm×7 mm×2 mm. The isolation of more than 20 dB was achieved with three absorber cells loaded between two loop antennas; interantenna spacing (center to center) is 0.23 λ0 at 2.54 GHz. The results show that port-to-port isolation between two antennas can be improved with absorber.